THE ROLE OF FEEDBACK IN INTENSIVE LANGUAGE LEARNING (Modern education and development, 2025)
mThis article explores the pivotal role of feedback in intensive language learning programs. It categorizes various types of feedback, including formative, summative, explicit, implicit, and source-based feedback (teacher, peer, and self-assessment), and examines how each contributes to language acquisition. The discussion highlights how immediate, clear, and balanced feedback accelerates learning, enhances motivation, and fosters learner autonomy in fast-paced environments. Best practices for providing effective feedback are outlined, emphasizing the importance of timely, personalized, and culturally sensitive responses. The article concludes by asserting that feedback remains a critical component of successful language education in both traditional and modern contexts.